1958
DOI: 10.1113/jphysiol.1958.sp006031
|View full text |Cite
|
Sign up to set email alerts
|

The effect of posterior pituitary hormones on the excretion of electrolytes, in dogs

Abstract: The oxytocic substance of posterior pituitary extracts is normally present in equal amounts in both sexes (van Dyke, Adamsons & Engel, 1955). So far two physiological functions have been ascribed to oxytocin, namely, as one of the factors causing contraction of the uterus in parturition, and as the factor responsible for contraction of the mammary myo-epithelial cells in lactation. Several workers have tried to find some other function for this substance. Positive results were obtained by Dicker & Heller (1946… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
62
2

Year Published

1961
1961
2009
2009

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(69 citation statements)
references
References 20 publications
5
62
2
Order By: Relevance
“…Geiling, DeLawder & Rosenfeld (1931) and Geiling & DeLawder (1932) have observed an increase in tissue metabolism and oxygen consumption with oxytocic preparations in unanaesthetized dogs, and have also reported that vasopressin and oxytocin have opposite metabolic effects. Fraser (1937) and Brooks & Pickford (1958) have shown that oxytocic preparations can antagonize the antidiuretic effect of the pressor hormone in rats and dogs. It is therefore postulated that the protective cardiac action of oxytocin observed in these experiments might be due to a metabolic action rather than to coronary dilatation.…”
Section: Discussionmentioning
confidence: 99%
“…Geiling, DeLawder & Rosenfeld (1931) and Geiling & DeLawder (1932) have observed an increase in tissue metabolism and oxygen consumption with oxytocic preparations in unanaesthetized dogs, and have also reported that vasopressin and oxytocin have opposite metabolic effects. Fraser (1937) and Brooks & Pickford (1958) have shown that oxytocic preparations can antagonize the antidiuretic effect of the pressor hormone in rats and dogs. It is therefore postulated that the protective cardiac action of oxytocin observed in these experiments might be due to a metabolic action rather than to coronary dilatation.…”
Section: Discussionmentioning
confidence: 99%
“…Early studies showed that i.v. administration of oxytocin raised the urinary excretion of sodium two to fourfold and enhance glomerular filtration rate in dogs (Brooks & Pickford 1958) and rats (Dicker & Heller 1946). Recent studies using Vp-deficient Brattleboro rats showed that these animals could respond dose-dependently to oxytocin.…”
Section: Anti-diuretic Action Of Oxytocinmentioning
confidence: 99%
“…In recent years, many studies have shown that other hormones also exhibit anti-diuretic functions and these findings add to a growing body of evidence indicating the involvement of Vp-independent mechanisms in regulating renal water reabsorption (Bauman 1965, Jeon et al 2003, Li et al 2006. Secretin (Waldum et al 1980, Chu et al 2007 and oxytocin (Brooks & Pickford 1958, Jeon et al 2003, were previously argued to exert either diuretic or antidiuretic effects, are therefore candidates in regulating renal functions. This review will focus on how these two hormones are potentially involved as Vp-independent mechanisms controlling water homeostasis.…”
Section: Introductionmentioning
confidence: 99%
“…This provides a tentative explanation for the pattern of electrolyte excretion seen in our experiments. Brooks & Pickford (1958) have shown that oxytocin causes natriuresis and kaluresis when it is given to conscious dogs at high rates of urine flow, if vasopressin is also present. During the early stages of water diuresis, when the plasma concentration of vasopressin is decreasing, the natriuretic effect of the circulating oxytocin would diminish.…”
Section: Discussionmentioning
confidence: 99%